Profile of Critical Thinking Skills of Grade VI Students - Wina Puspitasari; Peduk Rintayati; Moh Salimi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Critical thinking ability is an essential skill for students in facing the challenges of the 21st century. This study aims to find the level of student learning outcomes in the IPAS map and identify students' analytical skills in the IPAS map. The research method used is a descriptive quantitative approach with a one group pretest postest design. Data collection was carried out using a critical thinking ability test based on learning outcomes. The research method used is a quantitative approach with data collection techniques in the form of critical thinking skills tests based on two main indicators: interpretation, analysis. The research sample consisted of 49 students from three primary schools in the cluster. The results showed that the level of student learning outcomes was in the Good category with an average score of 83.38. A total of 89.8% of students scored in the 71-100 range, while the rest were in the Fair category, and no students were in the Poor category. In-depth analysis showed that the analysis aspect obtained an average score of 87.15 and interpretation 85.66, both of which were in the high category. This finding indicates that students have a strong ability to understand, decipher, and evaluate information in the context of IPAS learning. This research recommends the implementation of problem-based active learning strategies to develop critical thinking aspects more thoroughly and sustainably since primary education